The storm runner - Cervantes, Jennifer (Disney Hyperion, 2019)
To prevent the Mayan gods from battling each other and destroying the world, thirteen-year-old Zane must unravel an ancient prophecy, stop an evil god, and discover how the physical disability that makes him reliant on a cane also connects him to his father and his ancestry.